2004
DOI: 10.1118/1.1809991
|View full text |Cite
|
Sign up to set email alerts
|

The effects of target size and tissue density on the minimum margin required for random errors

Abstract: The minimum margins required to compensate for random geometric uncertainties in the delivery of radiotherapy treatment were determined for a spherical Clinical Target Volume, using an analytic model for the cumulative dose. Margins were calculated such that the minimum dose in the target would be no less than 95% of the prescribed dose for 90% of the patients. The dose distribution model incorporated two Gaussians, and could accurately represent realistic dose profiles for various target sizes in lung and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 22 publications
1
34
0
3
Order By: Relevance
“…The results were found to be consistent with the literatures’ expectations. Studies 28 , 29 , 30 have suggested if the tumor is irradiated at its average position during the respiratory cycle, optimal dose coverage would be obtained even if the tumor is not fully within the high‐dose region for a small part of the breathing cycle due to the presence of the wide‐beam penumbra. Moreover, dose planning performed at the end‐exhale phase was also suggested to maximize the target coverage with the most stable or reproducible target position.…”
Section: Discussionmentioning
confidence: 99%
“…The results were found to be consistent with the literatures’ expectations. Studies 28 , 29 , 30 have suggested if the tumor is irradiated at its average position during the respiratory cycle, optimal dose coverage would be obtained even if the tumor is not fully within the high‐dose region for a small part of the breathing cycle due to the presence of the wide‐beam penumbra. Moreover, dose planning performed at the end‐exhale phase was also suggested to maximize the target coverage with the most stable or reproducible target position.…”
Section: Discussionmentioning
confidence: 99%
“…This work focuses specifically on margins necessitated by geometric considerations. Margin recipes compromise between wide margins, which risk overdosing surrounding healthy tissue, and narrow margins, which risk underdosing the CTV (1)(2)(3)(4)(5). Margins are commonly held constant throughout treatment for all patients.…”
Section: Introductionmentioning
confidence: 99%
“…O fator densidade "mascara" tais estruturas, dificultando a sua localização. Além disso, a quantidade de ruídos presentes nas imagens cresce com a densidade dos tecidos (Witte et al, 2004;Zanetti-Dällenbach et al, 2008;Park et al, 2009).…”
Section: Lista De Figurasunclassified
“…Por fim, observando que o fator de risco de desenvolvimento de câncer de mama cresce acentuadamente de acordo com a densidade desse órgão (Boyd et al, 1995;Saha et al, 2001;Witte et al 2004;Malich et al, 2005) e que a reposição hormonal proporciona um incremento significativo na densidade do tecido mamário (Greemdale et al, 2003;Zanetti-Dällenbach et al, 2008;Yaffe, 2008), a performance dos esquemas CAD é efetivamente prejudicada por esses aspectos, que leva ao crescimento da taxa de detecção de falsos positivos (e, conseqüentemente, submissão desnecessária a processos invasivos, como biópsias).…”
Section: Lista De Figurasunclassified
See 1 more Smart Citation